Sodium Houttuyfonate Inhibits Bleomycin Induced Pulmonary Fibrosis in Mice - Shen, Yun-hui; Cheng, Ming-han; Liu, Xin-yu; Zhu, De-wei; Gao, Jian (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis (PF) can severely disrupt lung function with fatal consequences. However, there is currently no effective treatment for PF and idiopathic pulmonary fibrosis (IPF). The aim of this study was to investigate the effects of Sodium Houttuyfonate (SH) on bleomycin (BLM) induced PF mice model. Our results indicated that SH could attenuate BLM induced lung injury by reducing the inflammation, fibrogenesis and lung/body weight ratio. The proposed mechanisms for the protective effects of SH include: 1) improvement of pulmonary function in BLM mice, for instance, it can elevate the vital capacity (VC), 50% of forced expiratory flow (FEF50) and other pulmonary function indices; 2) inhibition of collagen formation in BLM mice; 3) attenuation of the elevation of inflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α), which are triggered by BLM administration; 4) reduction of the mRNA level and protein production of transforming growth factor-β1 (TGF-β1) in BLM mice. Furthermore, it was found that the protective effects of SH against BLM induced PF in mice was comparable to that of prednisone acetate (PA) tablets, a widely used drug for immunological diseases. Although Houttuynia Cordata Thunb has been widely used in China for lung infection and inflammation, the mechanisms and effective compounds have not yet been elucidated. Our study provides the evidence that SH is an effective compound against pulmonary injury, irritation and fibrogenesis.